Географічне поширення та умови зростання Adonis vernalis L. (Ranunculaceae Juss.) на території Мурафських товтр - Shynder, O.I. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2008)
The results of the study of geographical distribution and ecological and coenotical conditions of habitats rare and medical species Adonis vernalis L. in Murafa tovtrea. New two localities of Adonis vernalis L. – near Rusava Radjanka village in Tomashpil' district and near Bolgan village in Pishchanka district.